STUDENTS’ PERCEPTION TOWARDS THE APPLICATION OF SOCIAL MEDIA INSTAGRAM AS AN INSTRUCTIONAL MEDIA - Eilien Ivana Laksono; Ellyana Damayanti; Iman Santoso (IKIP Siliwangi, 2019)
In teaching learning, teachers can use a lot of instructional media for students. Instructional media in teaching learning is very significant. In this technological age, the use of social media began to be used in all fields of life, including education. One of the most popular social media for students is instagram. Nowdays everyone has instagram accounts, including students. The students usually use it to share their personal information, such as uploading their pictures or videos and writing instagram captions about their activity. Therefore, this study aims to find out students’ perception towards social media instagram as an instructional media for students of Smk TI Pembangunan Cimahi. In this research, the researchers used qualitative descriptive method, the data was obtained from questionaire and interview. The participants of this study were 30 students in SMK TI Pembangunan Cimahi at X Rpl A. The results of this study is social media instagram has high potential if it is used as an instructional media in vocational school. Because it can use for consulting with teacher, share material, giving announcement, media for quiz and for discussion. On the point of that, based on interview and questionaire can be known 80,7% of students agree and strongly agree that socaial media is used as an instructional media.